SISTEM INFORMASI ADMINISTRASI KEPENDUDUKAN (STUDI KASUS: DESA PARSAORAN AJIBATA KECAMATAN AJIBATA KABUPATEN TOBA SAMOSIR) - Novendra Adisaputra Sinaga; Sarida Sirait (Politeknik Bisnis Indonesia, 2019)
Parsaoran Sibisa Village, Ajibata is the village with the highest population density with a fairly high population movement in Ajibata Subdistrict, Toba Samosir Regency. At present the administrative system and population data activities are used by the filing method. Filing method is done by recording population data in population archive books, this method is less effective and efficient when there is a complex process of finding population data and population data reports. From these data it can be concluded that the problem in Parsaoran Ajibata Village is the lack of orderly administration of population so that population services are less effective and efficient. Therefore, the writer tries to offer a solution to build Population Administration Information System as Supporting Population Administration Order in Parsaoran Sibisa Village, Ajibata District, Toba Samosir Regency. Through assistance and training to the Village Government it will increase the knowledge and understanding of the importance of using Information Systems in terms of efficiency and effectiveness so that the Population Database in the Pisaoran Sibisa Village, Ajibata District is complete, accurate, and up to date.